Football must not forget its inclusive responsibilities in the rush to get fans back into stadiums - Brown, C. (Managing Sport and Leisure, 2020)
It is imperative that the English Premier League and the Football League clubs consider disabled supporters when planning for the return of fans in stadiums. While it is understandable that the English football clubs are eager to welcome fans back as soon as possible, I argue this must not be at the expense of disabled supporters. Utilising the theory of ableism, I highlight the inequitable matchday experiences of disabled football fans at the English Premier League and the Football League clubs pre-COVID-19, a situation I argue cannot be exacerbated by neglecting disabled fans as part of the return of fans to stadiums. This commentary emphasises the importance of English football clubs grasping the opportunity to positively change how disabled football fans are treated. The piece concludes by calling for sustained lobbying for inclusion, and the need for future research to focus and explicate the experiences of disabled football fans.